Dissecting the first and the second meiotic divisions using a marker-less drug-hypersensitive fission yeast - Aoi, Yuki (Landes Bioscience, 2014)
Faithful chromosome segregation during meiosis is indispensable to prevent birth defects and infertility. Canonical genetic manipulations have not been very useful for studying meiosis II, since mutations of genes involved in cell cycle regulation or chromosome segregation may affect meiosis I, making interpretations of any defects observed in meiosis II complicated. Here we present a powerful strategy to dissect meiosis I and meiosis II, using chemical inhibitors in genetically tractable model organism fission yeast (Schizosaccharomyces pombe). As various chemical probes are not active in fission yeast, mainly due to an effective multidrug resistance (MDR) response, we have recently developed a drug-hypersensitive MDR-sup strain by suppression of the key genes responsible for MDR response. We further developed the MDR-supML (marker-less) strain by deleting 7 MDR genes without commonly used antibiotic markers. The new strain makes fluorescent tagging and gene deletion much simpler, which enables effective protein visualization in varied genetic backgrounds. Using the MDR-supML strain with chemical inhibitors and live cell fluorescence microscopy, we established cell cycle arrest at meiosis I and meiosis II and examined Aurora-dependent spindle assembly checkpoint (SAC) regulation during meiosis. We found that Aurora B/Ark1 kinase activity is required for recruitment of Bub1, an essential SAC kinase, to unattached kinetochore in prometaphase I and prometaphase II as in mitosis. Thus, Aurora’s role in SAC activation is likely conserved in mitosis, meiosis I, and meiosis II. Together, our MDR-supML strain will be useful to dissect complex molecular mechanisms in mitosis and 2 successive meiotic divisions.